2019
DOI: 10.1111/sms.13532
|View full text |Cite
|
Sign up to set email alerts
|

Rescheduling Part 2 of the 11+ reduces injury burden and increases compliance in semi‐professional football

Abstract: Although the 11+ program has been shown to reduce injuries in sub‐elite football, program compliance is typically poor, suggesting that strategies to optimize delivery are necessary. This study investigated the effect of rescheduling Part 2 of the three‐part 11+ program on program effectiveness. Twenty‐five semi‐professional football clubs were randomly allocated to either a Standard‐11+ (n = 398 players) or P2post group (n = 408 players). Both groups performed the 11+ program at least twice a week throughout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
52
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 54 publications
(149 reference statements)
3
52
0
10
Order By: Relevance
“…Based on this, the Nordic hamstring exercise protocol showed a large and significant risk reduction (RR: 0.35, 95% CI 0.22 to 0.54; I 2 =0.0%) compared with usual care on hamstring injuries in football (n=1521) (high quality of evidence) 56 57. Data from individual studies62–65 are presented in table 2.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Based on this, the Nordic hamstring exercise protocol showed a large and significant risk reduction (RR: 0.35, 95% CI 0.22 to 0.54; I 2 =0.0%) compared with usual care on hamstring injuries in football (n=1521) (high quality of evidence) 56 57. Data from individual studies62–65 are presented in table 2.…”
Section: Resultsmentioning
confidence: 98%
“…In total 2468 studies were identified in the literature search. Three systematic reviews52–54 and 12 RCT’s was included 21 55–65. A systematic review and meta-analysis performed by van Dyk et al (2019) showed a medium and significant risk reduction (RR: 0.55, 95% CI 0.34 to 0.89; I 2 =67.0%) of hamstring injuries in football players in interventions including the Nordic hamstring exercise versus usual care (n=5362) (moderate quality of evidence) 53.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations